Cost Benefit Analysis of Procurement Systems and the Performance of Construction Projects in East Malaysia - Onosakponome, Odhigu Festus; ., Nazatul Shima Abdul Rani; ., Junaid M. Shaikh (Information Management and Business Review, 2011)
This research investigated the impacts of procurement systems on the performance of construction projects in East Malaysia. Construction project outcome may be measured in terms of time, cost and quality achieved. Project clients demand and want best value for their money and they want their projects to be completed on time, within budgeted cost and at appropriate quality or specification. The sample in this research consists of 58 participants that work in a construction companies/industry. 90 questionnaires were distributed, 69 were successfully returned and 58 were fully completed. The sample comprises project clients/owners, project managers, consultants and construction workers. However, due to the fact that the time allocated for this research is limited and it is of qualitative in nature for which the sample size is less important (Kumar, 2005). The aim of using project clients, project managers, consultants and construction workers from different companies is because they work under different circumstances, which will ensure all questions are answered from different perspective. Therefore, the researcher distributed questionnaires randomly among the participants in different construction companies. This also minimises any bias towards any particular company. The key findings and conclusions from literature review and the analysis of results of questionnaires issued to project clients, projects managers, consultants and construction workers showed that traditional procurement system benefits cost and quality but at the expense of time. In other words, traditional procurement system has positive impacts on project objectives of cost and quality and negative impact on project time. Design and build procurement system benefits cost and time but at the expense of quality and this implies that the impacts of design and build procurement system on project objectives of cost and time are positive with negative impact on project quality.